1987
DOI: 10.1002/joc.3370070504
|View full text |Cite
|
Sign up to set email alerts
|

Power spectra and coherence of drought in the interior plains

Abstract: Mean growing season (April-September) precipitation series at 407 stations in the Interior Plains of North America, dating back to 1985 in some stations, are used to derive a Bhalme and Mooley-type drought index for the region. Linear trend, representing first order non-stationarity, is first removed from the drought series. Then the periodogram via the Fast Fourier Transform (FFT), Maximum Entropy (ME) and Non-Integer (NI) spectral techniques are applied to search for significant periodicities in the temporal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 52 publications
2
19
0
Order By: Relevance
“…Cook et al (1997) also found evidence of a bidecadal drought rhythm in western North America since 1700. Despite the long-standing debate about whether solar or lunar cycles are responsible for these oscillations (Oladipo, 1987;Padmanabhan and Ramachandra Rao, 1990;Cook et al, 1997;Cerveny and Shaffer, 2001), no conclusive evidence exists (Thejll, 2001). No bidecadal oscillation was found in the June-July moisture spectra, and the 10-15 year peak is too broad to be linked directly to the 11 year sunspot cycle.…”
Section: Main Temporal Modes Of Moisture Variabilitymentioning
confidence: 96%
See 2 more Smart Citations
“…Cook et al (1997) also found evidence of a bidecadal drought rhythm in western North America since 1700. Despite the long-standing debate about whether solar or lunar cycles are responsible for these oscillations (Oladipo, 1987;Padmanabhan and Ramachandra Rao, 1990;Cook et al, 1997;Cerveny and Shaffer, 2001), no conclusive evidence exists (Thejll, 2001). No bidecadal oscillation was found in the June-July moisture spectra, and the 10-15 year peak is too broad to be linked directly to the 11 year sunspot cycle.…”
Section: Main Temporal Modes Of Moisture Variabilitymentioning
confidence: 96%
“…Quasi-biennial oscillations (QBOs) are a common feature in many time series from around the world, such as: precipitation (Oladipo, 1987), tree rings (Briffa et al, 1990), air temperature (Mason, 1976), SST (Allan, 2000), NAO (Hurrell, 1995;Allan, 2000), snow cover (Kane, 2000), and OLR (Kane, 2000). The cause of these QBOs is often attributed to reversals in stratospheric winds.…”
Section: Main Temporal Modes Of Moisture Variabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that only 50 spectral estimates are given in Figure 2(a and b), but 500 could have been computed in which case the spectra would be continuous curves. Following Currie's (1989) critique of Oladipo's (1987) improper procedures on North American rainfall records, CWO present numerous examples showing that fitting linear or higher order polynomials to data, and using the residuals to compute a spectrum, usually results in failure to detect the M, and S, terms. Figure 2(c) presents the spectrum of the residuals for dviA after a linear polynomial was fitted to the data by least squares.…”
Section: Maximum Entropy Spectramentioning
confidence: 99%
“…The goal is to describe time series in the time and frequency domains, including climatic teleconnections that can hardly be found within the correlation/regression approach. Although methods of multivariate time series analysis are also described, mostly in the frequency domain, in climatology (von Storch and Zviers, 1999) and oceanography (Emery and Thomson, 2004), they are rarely applied in both time and frequency domains (e.g., Privalsky, 1988;Privalsky and Jensen, 1995) or just in the frequency domain (e.g., Oladipo, 1987;Schneider and Schönwiese, 1989;Ghanbari et al, 2009;Park and Dusek, 2013).…”
Section: Introductionmentioning
confidence: 99%